Structural defects in 2D MoS2 nanosheets and their roles in the adsorption of airborne elemental mercury - Zhao, Haitao; Mu, Xueliang; Zheng, Chenghang; Liu, Shaojun; Zhu, Yanqiu; Gao, Xiang; Wu, Tao (2018)
In this research, ab initio calculations and experimental approach were adopted to reveal the mechanism of Hg0 adsorption on MoS2 nanosheets that contain various types of defects. The ab initio calculation showed that, among different structural defects, S vacancies (Vs) in the MoS2 nanosheets exhibited outstanding potential to strongly adsorb Hg0. The MoS2 material was then prepared in a controlled manner under conditions, such as temperature, concentration of precursors, etc., that were determined by adopting the new method developed in this study. Characterisation confirmed that the MoS2 material is of graphene-like layered structure with abundant structural defects. The integrated dynamic and steady state (IDSS) testing demonstrated that the Vs-rich nanosheets showed excellent Hg0 adsorption capability. In addition, ab initial calculation on charge density difference, PDOS, and adsorption pathways revealed that the adsorption of Hg0 on the Vs-rich MoS2 surface is non-activated chemisorption.